The Effect of Chaplain Patient Navigators and Multidisciplinary Family Meetings on Patient Outcomes in the ICU: The Critical Care Collaboration and Communication Project. (8th November 2021) - Alghanim, Fahid; Furqan, Muhammad; Prichett, Laura; Landon, Jondavid; Tao, Xueting; Selvam, Pooja; Leslie, Myles; Hartman-Shea, Katherine; Teague, Paula; Scott, Wayman; Kraeuter, Susan; Hicks, Heather; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To assess the effectiveness of a chaplain patient navigator in improving outcomes and reducing costs in the ICU setting. DESIGN: A randomized controlled trial at a large, urban, academic community hospital in Baltimore, Maryland. SETTING/PATIENTS: All patients admitted to the Johns Hopkins Bayview Medical Center Cardiac and Medical ICUs between March 2015 and December 2015. INTERVENTIONS: Patients in the intervention group were assigned a chaplain patient navigator to facilitate communication, offer support, and setup multidisciplinary family meetings. MEASUREMENTS AND MAIN RESULTS: The primary outcomes were hospital and ICU length of stay. Secondary outcomes included total and ICU charges, 60- and 90-day readmission rates, and the number of palliative care consults. For all outcomes, patients were included in the intention-to-treat analyses only if they remained in the ICU greater than 24 hours. In total, 1, 174 were randomly assigned to "usual care" ( n = 573) or to the intervention ( n = 601). In the intervention group, 44.8% (269/601) had meetings within 24 hours of admission and, of those patients, 32.8% (88/268) took part in the larger multidisciplinary family meeting 2–3 days later. The intervention group had longer mean adjusted hospital length of stay (7.78 vs 8.63 d; p ≤ 0.001) and mean ICU length of stay (3.65 vs 3.87 d; p = 0.029). In addition, they had greater total and ICU charges. There were no differences in other outcomes. Of note, only differences in total and ICU charges remained when controlling for case-mix index, which were greater in the intervention group. CONCLUSIONS: Although the chaplain patient navigator anecdotally enhanced communication, our study found an increase in hospital and ICU length of stay as well as cost. Since other studies have shown benefits in some clinical outcomes, projects focused on patient navigators may learn lessons from our study in order to better prioritize family meetings, gather indicators of communication quality, and identify the optimal patient navigator operational context.